Animal Biotechnology and Cultural Ecology - Kedi Suradisastra; Adriana M Lubis (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2000)
Animal biotechnology development is strongly related to historical contexts of animal production in a country and the receiving environment, particularly the existing cultural ecology. Cultural ecology influences both progress and process of adoption of such technology. A simulation on the technology’s discriminating power indicates that only those with sufficient techno-economic and social capability have greater possibility to adopt such a technology.   Key words: Biotechnology, cultural ecology, adoption